2009
DOI: 10.3329/jhpn.v27i3.3378
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Missed Vaccination during Mass Immunization Campaigns

Abstract: Achieving a high percentage of vaccination coverage with polio vaccine, while necessary, is not sufficient to eliminate or eradicate polio. The existence of pockets of under-vaccinated children has allowed outbreaks of polio in countries that have achieved high levels of vaccination coverage and in countries with no cases for many years. In a literature review, 35 articles were identified that described factors associated with missed vaccination in mass immunization campaigns. An annotated bibliography was dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 33 publications
0
18
0
2
Order By: Relevance
“…A medical home is a comprehensive approach to medical care with seven key elements: accessible, family-centered, continuous, comprehensive, coordinated, compassionate, and culturally effective care. 3 Although studies in the U.S. and elsewhere have identified many factors associated with underimmunization, including satisfaction, 1,[4][5][6][7][8][9][10][11][12][13][14] relatively little is known about how previous immunization experiences shape immunization patterns. While it is expected that children with strong medical homes will return regularly for well-child visits, completing their immunizations on time, we do not know what aspect of the medical home might be most influential in supporting this process.…”
mentioning
confidence: 99%
“…A medical home is a comprehensive approach to medical care with seven key elements: accessible, family-centered, continuous, comprehensive, coordinated, compassionate, and culturally effective care. 3 Although studies in the U.S. and elsewhere have identified many factors associated with underimmunization, including satisfaction, 1,[4][5][6][7][8][9][10][11][12][13][14] relatively little is known about how previous immunization experiences shape immunization patterns. While it is expected that children with strong medical homes will return regularly for well-child visits, completing their immunizations on time, we do not know what aspect of the medical home might be most influential in supporting this process.…”
mentioning
confidence: 99%
“…Although some of the reasons for nonparticipation in the most recent NIDs were similar to those identified in other countries (for example, lack of information about the campaign and operational issues) [12,17,18], the main reasons given for nonparticipation suggested that parents of children who were not vaccinated in NIDs did not value the campaign or felt that the child's participation was unnecessary. These opinions may have been influenced by advice from health professionals.…”
Section: Discussionmentioning
confidence: 78%
“…A more thorough field study on the role of social factors can help in the design of better policies. Factors such as gender, caste, and wealth should also be investigated and addressed [26,45].…”
Section: Discussionmentioning
confidence: 99%
“…Since 9/11, Pakistan has been facing a critical threat to its security. Rising insurgency in the tribal areas of KPK have caused the armed forces to retaliate [26]. Extremist groups in KPK have fragmented into many subgroups, leading to many terrorist activities in almost all major parts of the country.…”
Section: Securitymentioning
confidence: 99%
See 1 more Smart Citation